Original article Abnormal chaperone-mediated autophagy (CMA) - Fidziańska, Anna; Walczak, Ewa; Walski, Michał (Folia Neuropathologica, 2007)
Ultrastructural analysis of the cardiomyocyte structure in Danon disease reveals dramatic accumulation of abnormal late autophagic vacuoles (AVd) suggestive of primary lysosomal defect. Moreover, the accumulation of AVd in cardiomyocytes is consistent with a decreased rate of autophagic to lysosomal trafficking. These results suggest that the loss of the LAMP-2 protein strongly inhibits uptake of proteins into lysosomes for degeneration. The significant reduction of chaperone-mediated autophagy (CMA) activity in the affected cardiomyocytes induces a dramatic increase in the number and size of AVd and a severe reduction of myocardial contractility.